Does maximum strength predict rowing performance in elite female rowers? - Behm, S.; Jacobs, M. W.; Schumann, M. (International Journal of Sports Physiology and Performance, 2024)
Purpose: This study aimed to identify dynamic free-weight exercises for strength training and testing that are strong determinants of specific rowing ergometer performance measures in elite female rowers.